Amelogenins as Potential Buffers during Secretory-stage Amelogenesis. (March 2015) - Guo, J.; Lyaruu, D.M.; Takano, Y.; Gibson, C.W.; DenBesten, P.K.; Bronckers, A.L.J.J.
Amelogenins are the most abundant protein species in forming dental enamel, taken to regulate crystal shape and crystal growth. Unprotonated amelogenins can bind protons, suggesting that amelogenins could regulate the pH in enamel in situ. We hypothesized that without amelogenins the enamel would acidify unless ameloblasts were buffered by alternative ways. To investigate this, we measured the mineral and chloride content in incisor enamel of amelogenin-knockout ( AmelX -/- ) mice and determined the pH of enamel by staining with methyl-red. Ameloblasts were immunostained for anion exchanger-2 (Ae2), a transmembrane pH regulator sensitive for acid that secretes bicarbonate in exchange for chloride. The enamel of AmelX -/- mice was 10-fold thinner, mineralized in the secretory stage 1.8-fold more than wild-type enamel and containing less chloride (suggesting more bicarbonate secretion). Enamel of AmelX -/- mice stained with methyl-red contained no acidic bands in the maturation stage as seen in wild-type enamel. Secretory ameloblasts of AmelX -/- mice, but not wild-type mice, were immunopositive for Ae2, and stained more intensely in the maturation stage compared with wild-type mice. Exposure of AmelX -/- mice to fluoride enhanced the mineral content in the secretory stage, lowered chloride, and intensified Ae2 immunostaining in the enamel organ in comparison with non-fluorotic mutant teeth. The results suggest that unprotonated amelogenins may regulate the pH of forming enamel in situ. Without amelogenins, Ae2 could compensate for the pH drop associated with crystal formation.